Determination and inheritance of phytic acid as marker in diverse genetic group of bread wheat - Ahmad, Ijaz; Mohammad, Fida; Zeb, Aurang; Noorka, Ijaz R.; Farhatullah; Jadoon, Sultan A. (Scientific Research Publishing, 2013)
Phytic acid (Myo-inositol 1,2,3,4,5,6 hexa-kisphophate) is a storage form of phosphorus and can accumulate to the levels as high as 35% in the wheat kernel. Phytic acid acts as an inhibitor for macronutrients as well as micronutrients and located in the bran of wheat kernel. Due to its inhibitory role, a high concentration of phytic acid is undesirable as it hinders the bio-availability of some essential nutrients such as Fe, Mg, Ca, Zn and Cu, etc. In order to check the inheritance of phytic acid in wheat kernels, phytic acid concentration was initially determined in kernels of 10 wheat genotypes to identify two contrasting genetic groups for diallel analysis. Based on pre-screening results of 10 wheat genotypes, five wheat genotypes (3 with high and 2 with low phytic acid concentration) were crossed in all possible combinations during 2007-2008 by 5 × 5 full diallel mating fashion to insight the inheritance of phytic acid and other yield contributing traits. All 20 F1 hybrids and five parental genotypes revealed significant differences statistically, except plant maturity. The narrow and broad sense heritability estimates varied widely among traits for spike length (0.17, 0.62), spikelets spike-1 (0.35, 0.74), tillers plant-1 (0.05, 0.52) and phytic acid concentration (0.01, 0.86). The values for phytic acid concentration ranged from 0.56% to 3.43% among F1 hybrids and 1.06 to 3.67% for parental genotypes. F1 hybrids, Ps-2005 × Ghaznavi (0.56%), AUP-4006 × Ps-2004 (0.74%), Janbaz × Ps-2004 (0.89%) and Janbaz × Ps-2005 (1.01%), had the lowest concentration of phytic acid. The study concluded that F1 hybrids with low phytic acid concentration could yield desirable segregants.
Keywords: Phytic Acid; Diallel Analysis; Inheritance; Heritability; Yield; Traits